PENERAPAN STRATEGI REACT UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN STOIKIOMETRI DI KELAS X SMA NEGERI 1 KAMPAR - Bella Oktari; R. Usman Rery; Roza Linda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purposes of this research was to know the differences between the application of REACT strategy and conventionally on the stoichiometry subject at the class X senior high school 1 Kampar. REACT strategy includes five steps Relating, Experiencing, Applying, Cooperating, and Transferring. This research used quasi experiment with design Randomized Control Group Pretest-Posttest. The sample of research consisted two class, class X MIPA 3 and class X MIPA 4. The analysis for normality data used Kolmogorov-Smirnov test obtained results that was normally distributed and homogeneity test used Levene test obtained results that was homogeneous. The analysis data used Independent-Sample T-Test, the result shows there was significancy differences between REACT strategy and conventionally were student achievement who learn used REACT strategy have improve significancy on stoichiometry subject (t = 3,207. Sig = 0,002).Key Words : REACT strategy, Learning Achievement, Stoichiometry